2021
DOI: 10.1177/0034523720984200
|View full text |Cite
|
Sign up to set email alerts
|

Attending to data: Exploring the use of attendance data within the datafied school

Abstract: Contemporary schooling is seen to be altering significantly in light of a combined ‘digitisation’ and ‘datafication’ of key processes. This paper examines the nature and conditions of the datafied school by exploring how a relatively prosaic and longstanding school metric (student attendance data) is being produced and used in digital form. Drawing on empirical data taken from in-depth qualitative studies in three contrasting Australian secondary schools, the paper considers ‘anticipatory’, ‘analytical’ and ‘a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Rather, through describing the initial steps of working with school practitioners, our goal is to provide examples of how researchers and practitioners could work together to turn data into useful information for knowledge generation. Given the recent sobering research that has indicated that Step 2 of the data use cycle may be a problematic sticking point for many schools (Selwyn et al , in press; Farley-Ripple et al , 2021; Wayman et al , 2017), our results highlight how data science workflows (Agasisti and Bowers, 2017; Krumm et al , 2018) can be integrated into current ongoing improvement cycles within a school or district to help address the needs of practitioners. It is our contention that collaborative educational data science (Bowers et al , 2019; Bowers, 2017; Piety, 2019; Piety et al , 2014; Agasisti and Bowers, 2017) can and should be included within the logic model of data use in schools.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Rather, through describing the initial steps of working with school practitioners, our goal is to provide examples of how researchers and practitioners could work together to turn data into useful information for knowledge generation. Given the recent sobering research that has indicated that Step 2 of the data use cycle may be a problematic sticking point for many schools (Selwyn et al , in press; Farley-Ripple et al , 2021; Wayman et al , 2017), our results highlight how data science workflows (Agasisti and Bowers, 2017; Krumm et al , 2018) can be integrated into current ongoing improvement cycles within a school or district to help address the needs of practitioners. It is our contention that collaborative educational data science (Bowers et al , 2019; Bowers, 2017; Piety, 2019; Piety et al , 2014; Agasisti and Bowers, 2017) can and should be included within the logic model of data use in schools.…”
Section: Discussionmentioning
confidence: 86%
“…Recent examples include low engagement by educators in popular data systems such as NWEA MAP (Farley-Ripple et al , 2021), few if any significant relationships between teacher instructional clicks in a data dashboard and student outcomes in a large US school district (Wayman et al , 2017) and a tendency to reify problematic inferences about student knowledge and learning when observing teacher data team meetings to discuss individual student assessment answer data (Garner et al , 2017). An issue rarely noted throughout the literature on school data use was recently highlighted by Selwyn et al (in press) in that more often than not “data analytics” takes the form of having the “data person” in the school work in spreadsheets to create “simple frequency counts, color-coding and modest cross-tabulations” (p. 13). Moreover, technological tools that were intended to support more inspired data analysis were, according to Selwyn and colleagues:…”
Section: A Theory Of Action For Data Use In Schoolsmentioning
confidence: 99%
See 3 more Smart Citations